1989
DOI: 10.1128/mcb.9.7.2798
|View full text |Cite
|
Sign up to set email alerts
|

A bcr-v-abl oncogene induces lymphomas in transgenic mice.

Abstract: In chronic myeloid leukemia and some cases of acute lymphoblastic leukemia, a 9;22 chromosome translocation has fused most of the c-abl oncogene to a gene designated bcr. To explore in vivo the biological effects of the chimeric gene, we introduced a facsimile of the translocation product, a bcr-v-abl gene, into the mouse germ line under the control of the immunoglobulin heavy-chain enhancer or a retroviral long terminal repeat. Some transgenic mice bearing either construct developed clonal lymphoid tumors. T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(84 citation statements)
references
References 55 publications
5
78
0
1
Order By: Relevance
“…M1 cells were co-transfected with the MPZen(bcr ± abl) provirus (Hariharan et al, 1988) and a puromycin resistance plasmid to obtain M1 cell lines stably expressing BCR ± ABL. The MPZen(bcr ± abl) provirus incorporates the BCR ± ABL cDNA cloned from the human CML cell line K562 and encodes the 210 kD form of the BCR ± ABL protein.…”
Section: Generation Of Bcr ± Abl-expressing M1 Clonesmentioning
confidence: 99%
“…M1 cells were co-transfected with the MPZen(bcr ± abl) provirus (Hariharan et al, 1988) and a puromycin resistance plasmid to obtain M1 cell lines stably expressing BCR ± ABL. The MPZen(bcr ± abl) provirus incorporates the BCR ± ABL cDNA cloned from the human CML cell line K562 and encodes the 210 kD form of the BCR ± ABL protein.…”
Section: Generation Of Bcr ± Abl-expressing M1 Clonesmentioning
confidence: 99%
“…Southern blots of HindIII or EcoRI digested DNA (10 mg) were hybridized with a 32 Plabelled 2 kb EcoRI fragment encompassing the TCR Jb2 region or a 670 bp PstI ± NaeI fragment spanning the J H4 region of the Igh gene (Hariharan et al, 1989). RNA was extracted with 4M guanidine thiocyanate and the polyadenylated fraction puri®ed by oligo(dT)-cellulose chromatography (Alexander et al, 1995).…”
Section: Nucleic Acid Analysismentioning
confidence: 99%
“…The first BCR/ABL transgenic mice expressed a BCR/vabl facsimile oncogene (similar to p210 BCR/ABL) under the immunoglobulin heavy-chain enhancer (Eµ) or the widely expressed promoter/enhancer from the long terminal repeat (LTR) of the murine myeloproliferative sarcoma virus (MPSV) [15]. There was a decreased yield of transgenic offspring from eggs injected with either transgene DNA, but a small number of transgenic founders of both types, and some progeny developed clonal T and B lymphomas.…”
Section: Conventional Bcr/abl Transgenic Micementioning
confidence: 99%
“…Activated ABL genes are known to have cytotoxic effects, and the presence of the transgene in all tissues raises the possibility of toxicity during embryonic development. Toxicity was initially suggested by the inefficient generation of BCR/v-abl transgenic founders and the failure of this transgene to express prior to development of overt malignancy [15], whereas a subsequent study directly confirmed that a BCR/ABL transgene expressed from the BCR promoter caused embryonic lethality [30]. The δMT-1 promoter should be expressed in myeloid progenitors, but this promoter may be downregulated in these transgenic mice because of transgene toxicity, and the resulting low levels of BCR/ABL expression are below a threshold required for oncogenic transformation by tyrosine kinases.…”
Section: Limitations Of Bcr/abl Transgenic Micementioning
confidence: 99%